2021
DOI: 10.1159/000520651
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sex-Mismatched Red Blood Cell Transfusion on Endothelial Cell Activation in Critically Ill Patients

Abstract: <b><i>Background:</i></b> Observational studies suggest that sex-mismatched transfusion is associated with increased mortality. Mechanisms driving mortality are not known but may include endothelial activation. The aim of this study is to investigate the effects of sex-mismatched red blood cell (RBC) transfusions on endothelial cell activation markers in critically ill patients. <b><i>Study Design and Methods:</i></b> In patients admitted to the intensive care un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Despite the patient receiving several platelet transfusions, although it is difficult to prove unequivocally that SDC-1 levels are unaffected by platelet concentrate transfusion, there is currently no clear evidence that they increased serum SDC-1 concentrations, and as such we believe that their effect on values is limited ( 30 , 31 ). With regards to erythrocyte transfusions however, a previous study demonstrated that transfusion of a single sex-mismatched RBC unit was associated with higher SDC-1 levels than transfusion of a sex-matched RBC unit ( 32 ). Finally, as the patient required intensive care and various medications were administered, it is likely that drugs affected the patient, and future studies are needed to delineate the specific impact.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the patient receiving several platelet transfusions, although it is difficult to prove unequivocally that SDC-1 levels are unaffected by platelet concentrate transfusion, there is currently no clear evidence that they increased serum SDC-1 concentrations, and as such we believe that their effect on values is limited ( 30 , 31 ). With regards to erythrocyte transfusions however, a previous study demonstrated that transfusion of a single sex-mismatched RBC unit was associated with higher SDC-1 levels than transfusion of a sex-matched RBC unit ( 32 ). Finally, as the patient required intensive care and various medications were administered, it is likely that drugs affected the patient, and future studies are needed to delineate the specific impact.…”
Section: Discussionmentioning
confidence: 99%
“…Implicated cytokines and chemokines include IFN-γ, IL-6 and IL-8,32 33 which differed between the transfusion exposure groups in the current study. Donor sex-related immunomodulation, with increases in proinflammatory cytokines, also contributes to endothelial activation, a potential predictive marker for transfusion-associated adverse outcomes and recently shown to be increased with sex-mismatched PRBC exposure 34…”
Section: Discussionmentioning
confidence: 99%
“…Donor sex related immunomodulation, with increases in pro-inflammatory cytokines, also contributes to endothelial activation. This is a potential predictive marker for transfusion associated adverse outcomes and has recently been shown to be increased with sex mismatched RBC transfusion exposure [ 69 ]. In vitro data supports the release of markers of endothelial activation following the incubation of endothelial cells with blood product supernatant [ 70 , 71 ].…”
Section: How Might Donor Sex Influence Outcome?mentioning
confidence: 99%
“…The link between transfusion exposure and endothelial activation may be directly related to post-transfusion increases in pro-inflammatory cytokines [ 73 ], a response observed in the preterm newborn [ 43 , 44 ], or due to the presence of free heme and non-transferrin bound iron [ 74 , 75 ]. Recently, Alshalani and colleagues reported significantly greater post-transfusion concentrations of syndecan-1 and soluble thrombomodulin in adult intensive care patients who received a single sex-mismatched RBC transfusion compared to those who received sex-matched blood [ 69 ]. Critically, both syndecan-1 and soluble thrombomodulin are known predictors of in-hospital mortality [ 76 ].…”
Section: How Might Donor Sex Influence Outcome?mentioning
confidence: 99%